2001
DOI: 10.3923/jbs.2001.401.411
|View full text |Cite
|
Sign up to set email alerts
|

Production Physiology of Cellulases and β-glucosidase Enzymes of Aspergillus niger Grown under Solid State Fermentation Conditions

Abstract: A new isolate of A. niger F-119 was utilizaed to produce endoglucanase (EC 3. 21. 4) exoglucanase (EC 3. 2. 1. 91) and 13-glucosidase (EC 3. 2. 1. 21) adopting the solid state fermentation condition using radicle waste as main substrate. Cultural conditions including moisture level, incubation period, initial pH, incubation temperature and inoculum size were evaluated. The fungus expressed high enzymes production at moisture level 70% (w /w), initial pH 4.5, inoculum size 10% (v/w) at 32EC after 72h which yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Vu et al [30] noted that substrate weight 3% is the most suitable percent when he used wheat bran to produce cellulase from Aspergillus niger . Fadel and Kahil [38] reported that 2% was the best, they used alkali treated cotton stalks for producing cellulose and hemicelluloses degrading enzyme by A. niger F-93 [39], as well as the same ratio was found by Fadel [39] when he produced xylanase from fermented sorghum flour by Trichoderma harizinum 418.…”
Section: Effect Of Aeration On Alkaline Cellulase Production By a Fumigatus Mutant-17mentioning
confidence: 86%
See 1 more Smart Citation
“…Vu et al [30] noted that substrate weight 3% is the most suitable percent when he used wheat bran to produce cellulase from Aspergillus niger . Fadel and Kahil [38] reported that 2% was the best, they used alkali treated cotton stalks for producing cellulose and hemicelluloses degrading enzyme by A. niger F-93 [39], as well as the same ratio was found by Fadel [39] when he produced xylanase from fermented sorghum flour by Trichoderma harizinum 418.…”
Section: Effect Of Aeration On Alkaline Cellulase Production By a Fumigatus Mutant-17mentioning
confidence: 86%
“…(NH4)2SO4 was used for cellulase production under solid state and submerged cultures from culturing many fungal strains i.e. Trichoderma harizianum, Penicillium funiculosum, Aspergillus niger, Fusarium dimerum and Rhizopus oryyzae [35,38,39,41].…”
Section: Effect Of Nitrogen Source On Alkaline Cellulase Production By a Fumigatus Mutant-17mentioning
confidence: 99%
“…on combination of CH 3 COONH 3 0.35%, (NH 4 ) 2 SO 4 0.7% and KH 2 PO 4 0.4%. Introduction of ammonium sulphate at 2% N (w/w) enhanced extracellular soluble protein/g of substrate by A. niger in comparison to control by about 13.6% (Fadel 2000). This increase in soluble proteins was accompanied by increase to the extent of 21.3, 21.5 and 20% in the activity of FPase, CMCase and β-glucosidase respectively.…”
Section: Effect Of Nitrogen Sources On β-Glucosidase Productionmentioning
confidence: 89%
“…The optimum temperature 32 o C was recorded for the maximum production of cellulolytic enzymes by A. niger F-119 on radicle wastes (Fadel 2000). Badhan et al, 2007 showed that the incubation temperature at 45 o C was found to be optimum for production of cellulolytic enzymes by Myceliophthora sp.…”
Section: Effect Of Temperaturementioning
confidence: 96%
“…Virtually, information on the effect of thickness of bed of solid medium on enzyme production in SSF is lacking. The influence of depth of solid medium on production of cellulolytic enzyme by A. niger in SSF has been assessed (Fadel 2000). According to this study, production of cellulases and β-glucosidases by A. niger on radicle waste increased slightly until 12 mm, was steady to 18 mm, and then decreased.…”
Section: Depth Of the Substratementioning
confidence: 99%